2019
DOI: 10.1002/jsde.12366
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactants from Waste: Structures and Interfacial Properties of Sophorolipids Produced from a Residual Oil Cake

Abstract: Sophorolipids (SL) are microbial biosurfactants that have entered the market as detergent and cosmetic formulation ingredients. Current research is focused on the use of wastes to decrease the final production costs of SL and the environmental impacts. SL from wastes will help to move toward the circular economy only if the SL produced this way are pure enough and as efficient as current commercial SL. This manuscript focuses on the study of the structures and the interfacial properties of a crude SL natural m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 23 publications
2
15
0
1
Order By: Relevance
“…Moreover, most are obtained from the food processing industry, with few restrictions regarding use for the growth of microorganisms and the subsequent production of biosurfactants that can be employed in the food, cosmetic, agrochemical, and pharmaceutical industries. 81,82 Thus, the use of waste products is not only advantageous due to the reduction in substrate costs but also due to the availability and stability of each substrate, which are determinants of the quantity to be used, form to be applied (solid or liquid), particle size, texture and even the packaging, transport, storage, stability, and purity, as all these factors exert an influence on the formulation of any production medium. 65,83…”
Section: Production Of Biosurfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, most are obtained from the food processing industry, with few restrictions regarding use for the growth of microorganisms and the subsequent production of biosurfactants that can be employed in the food, cosmetic, agrochemical, and pharmaceutical industries. 81,82 Thus, the use of waste products is not only advantageous due to the reduction in substrate costs but also due to the availability and stability of each substrate, which are determinants of the quantity to be used, form to be applied (solid or liquid), particle size, texture and even the packaging, transport, storage, stability, and purity, as all these factors exert an influence on the formulation of any production medium. 65,83…”
Section: Production Of Biosurfactantsmentioning
confidence: 99%
“…Studies have shown that these waste products can be used as carbon and nitrogen sources, enabling the acquisition of biosurfactants with desirable properties. Moreover, most are obtained from the food processing industry, with few restrictions regarding use for the growth of microorganisms and the subsequent production of biosurfactants that can be employed in the food, cosmetic, agrochemical, and pharmaceutical industries 81,82 …”
Section: Biosurfactantsmentioning
confidence: 99%
“…A percepção em relação aos subprodutos agrícolas têm sido reavaliada ao longo dos anos e estes vem, cada vez mais, sendo considerados recursos valiosos. Estes materiais são ricos principalmente em açúcares, fibras e outros materiais hidrolisáveis e fermentáveis, sendo, portanto, passíveis de utilização para a produção de enzimas (Da De Menezes et al, 2016), oligossacarídeos , bioetanol , biossurfactantes (Fai et al, 2015b;Marti et al, 2015;Jiménez-Peñalver et al, 2019), biopeptídeos (Hafeez et al, 2014;Mechmeche et al, 2017), biopolímeros (Fai et al, 2011;Koutinas et al, 2014), entre outros, como pode ser observado na Tabela 3. Research, Society and Development, v. 9, n. 7, e588974488, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i7.4488…”
Section: Substratos Alternativosunclassified
“…[7] The differences of SLs structures are dependent on the degree of acetylation, the length of carbon chain, the unsaturation of fatty acids, and internal esterification, which further determined the properties of SLs. [8][9][10] Therefore, SLs fermentation process is a complex multiphase system of gas, liquid, and solid, not only containing SLs with different structural properties (solid crystallization, oily, etc. ), but also possessing bubbles, lipids, glucose, cells, and other substances in the fermentation broth.…”
Section: Introductionmentioning
confidence: 99%